Leading the teacher team – balancing between formal and informal power in program leadership. Issue 1 (2nd January 2018) - Högfeldt, Anna-Karin; Malmi, Lauri; Kinnunen, Päivi; Jerbrant, Anna; Strömberg, Emma; Berglund, Anders; Villadsen, Jørgen
Abstract : This continuous research within Nordic engineering institutions targets the contexts and possibilities for leadership among engineering education program directors. The IFP-model, developed based on analysis of interviews with program leaders in these institutions, visualizes the program director's informal and formal power. The model is presented as a tool for starting a shared discussion on the complexities of the leadership of engineering program development. The authors liken program development to hunting in teams. Each individual expert in the program is needed, and all experts will need to work and collaborate for the same target. This calls for strategic and long-term thinking of engineering education development. Institutions should support the development of both formal structures as well as informal leadership skills among their program directors, but never fall for the temptation to see the program director as the only actor on the stage.